IDENTIFIKASI POTENSI DAN PERMASALAHAN DESA TANGLAPUI TIMUR SEBAGAI DASAR PENGEMBANGAN PEMBANGUNAN PEDESAAN - Lambertus Lupuikoni; Isak Fantang; Imanuel M. Laukamang; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
Tanglapui Timur Village has significant potential in the agriculture, plantation, forestry, tourism, and local cultural sectors. However, the village also faces several challenges, such as low quality education, limited infrastructure, environmental damage, limited access to clean water, and the risk of natural disasters. This qualitative descriptive research aims to identify the village's potential and challenges as a basis for developing recommendations for sustainable rural development. Data were obtained through observation, interviews, and documentation. The results indicate that although the village possesses significant natural and cultural riches, structural and social challenges need to be addressed through targeted development planning based on community participation. This article provides a comprehensive analysis and strategic recommendations for village development in accordance with the principles of sustainable rural development.